Riparian Vegetation and Invasive Species in the Boyong River, Yogyakarta - Sulistiyowati, Eka; Pramesti, Dias Idha; Hidyatulah, Abdul Rafi; Hayati, Asya Nur; Amal, Ilham Ikhlasul (Jurnal Biologi Tropis, 2026)
Riparian ecosystem in Boyong river represents an urban stream ecosystem exposed to multiple environmental pressures, including agricultural runoff, domestic wastewater discharge, and periodic post-eruptive material flows originating from Mount Merapi. The study was conducted through vegetation exploration and macrophyte species identification across several river segments (n sites= 3). The results revealed that the macrophyte community was predominantly composed of herbaceous and shrub species with high tolerance to environmental disturbances (the number of species =259). Native non-invasive plant species were relatively limited in number, whereas several introduced species exhibited high invasive potential within the riparian zone. These findings indicate the presence of ecological pressures that influence vegetation community structure and potentially contribute to the degradation of river ecosystem quality. This study provides preliminary ecological information on the condition of the Boyong River and highlights the importance of riparian vegetation management and invasive species control to maintain the ecological health of urban river ecosystems.